Smart irrigation control using inexpensive capacitance probes - Shahidian, Shakib (2015)
The mass marketing of inexpensive capacitance probes has opened the door for development of smart irrigation controllers based on soil moisture content. The advantage over climate based irrigation is that these systems are easier to use and can compensate for rainfall and variations in the irrigation system application rate. In this work, a smart irrigation controller was developed using EC-5 Echo sensors connected to Siemens LOGO microcontrollers to start the irrigation process. The system was validated in a lettuce crop grown in a greenhouse in southern Portugal. The sensors were buried 10 cm in the center of mini-lysimeters with four different trigger points: 25, 22, 20 and 17% volumetric soil moisture, and the irrigation depth set to replenish the soil to field capacity. The results indicate that the main challenge to soil irrigation control is the precise location of the sensor in relation to the drippers. In this work no significant differences in crop yield were observed between the three treatments, although there was a water economy of some 5% when using the lower trigger point, possibly due to smaller losses from soil evaporation.